PENGARUH PRODUKSI, KURS DOLLAR AS, DAN INFLASI TERHADAP EKSPOR BUAH MANGGIS INDONESIA - Sasmita, Kadek Chandra Ayu; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 8 (2022): VOL11NO 8, AGUSTUS 2022 [2900-3323]DO - 10.24843/EEP.2022.v11.i08.p10, 2022)
Indonesia is an agricultural country, meaning agricultural sub-sector that has the potential to continue to be developed. A fruit commodity has good market potential to continue developed is mangosteen which is a type of fruit has become the prima donna Indonesia's exports. This research to analyze effect of production, the US dollar exchange rate, and inflation simultaneously, partially and the independent variables which had the most dominant influence on the export of Indonesian mangosteen fruit. The data uses from 2012 - 2019 in the quarter obtained from BPS, Ministry of Agriculture, and BI. The method used multiple linear regression analysis using with SPSS program. The analysis shows that simultaneously production, US dollar exchange rate, and inflation have significant effect on the export of Indonesian mangosteen fruit. Partially production variable has positive significant effect on Indonesian mangosteen fruit exports, the dollar exchange rate variable doesn’t have positive significant effect on Indonesian mangosteen fruit exports, and the inflation variable has  negative and significant effect on Indonesia's mangosteen fruit exports. Then, the variable that most dominantly affects the export of Indonesian mangosteen is the production variable Key words : mangosteen fruit export, production, US dollar exchange rate, inflation